Biowaiver Monographs for Immediate‐Release Solid Oral Dosage Forms: Codeine Phosphate. Issue 6 (1st May 2014) - Dahan, Arik; Wolk, Omri; Zur, Moran; Amidon, Gordon L.; Abrahamsson, Bertil; Cristofoletti, Rodrigo; Groot, D. W.; Kopp, Sabine; Langguth, Peter; Polli, James E.; Shah, Vinod P.; Dressman, Jennifer B.
<x xml:space="preserve">Abstract</x> The present monograph reviews data relevant to applying the biowaiver procedure for the approval of immediate‐release multisource solid dosage forms containing codeine phosphate. Both biopharmaceutical and clinical data of codeine were assessed. Solubility studies revealed that codeine meets the "highly soluble" criteria according to World Health Organization (WHO), the European Medicines Agency (EMA), and the United States Food and Drug Administration (US FDA). Codeine's fraction of dose absorbed in humans was reported to be high (>90%) based on cumulative urinary excretion of drug and drug‐related material following oral administration. The permeability of codeine was also assessed to be high in both Caco‐2 monolayers and rat intestinal perfusion studies. The main risks associated with codeine, that is, toxicity (attributed to CYP2D6 polymorphism) and its abuse potential, are present irrespective of the dosage form, and do not need to be taken into account for bioequivalence (BE) considerations. Taken together, codeine is a class 1 drug with manageable risk and is a good candidate for waiver of in vivo BE studies. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci